PERBEDAAN TINGKAT KONSUMSI VITAMIN C SEBELUM DAN SELAMA PANDEMI COVID-19 PADA MAHASISWA TEKNIK RADIOLOGI STIKES AWAL BROS PEKANBARU - Aulia Annisa; Febi Ernanda Mauliza; Hema Susanti; Violita Yani Putri (Medical Imaging and Radiation Protection Research Journal, 2021)
This study will discuss several things, namely the understanding of vitamin c, the benefits of vitamin c, sources of vitamin c, the relationship with the pandemic and the level of vitamin consumption in students. This type of research is quantitative, using a questionnaire survey approach and the research design is comparative. The research variables in this study were the dependent variable (Radiology Engineering student semester IV Stikes Awal Bros Pekanbaru), independent variable 1 (before the pandemic) and independent variable 2 (during the pandemic). Determination of the number of samples in this study using all students in the fourth semester of STIKes Awal Bros Pekanbaru, totaling 55 people. Data processing is carried out using Google Forms by retrieving data using questionnaires distributed to respondents in the form of positive questions and negative questions so that answers are obtained. The data analysis technique used is the instrument test, the customer satisfaction index and the Friedman test. Based on the results of this study, the researchers concluded that there are still many students of STIKES AWAL BROSS PEKANBARU who have not realized the importance of consuming vitamin C. During a pandemic like this, it is highly recommended to consume vitamin C sufficiently and regularly. There are still many PEKANBARU STIKES AWAL BROSS students who do not consume vitamin C during the current pandemic.